Comparative evaluation of the compressive strength surface hardness and porosity of a selection of capsule-mixed versus hand-mixed Glass lonomer cements - Brandt, Paul Dieter (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2019.